Analysis of Language Style in Utsman bin Affan's First Sermon Post Heartball: Taḥlīl Uslūb al-Lughah fī Khuṭbah ‘Uthmān ibn ‘Affān al-Ūlā ba‘da al-Ighmā’ - Raudhatul Jannah; Kurnia, Ulfa; Perdana, Dyah Adila (An-Nahdah Al-'Arabiyah is published by Department of Arabic Language and Literature in cooperation with The Center for Research and Community Service (LP2M), 2026)
This study examines the stylistic beauty of Uthman ibn Affan's first sermon after his appointment as the third caliph by highlighting five main aspects, namely phonology, morphology, syntax, semantics, and imagery. This study uses a qualitative approach with a stylistic analysis method on the Arabic sermon text which is studied descriptively-analytical. The results show that the dominance of nasal and vibrating consonants forms a distinctive phonological rhythm that strengthens the persuasive power of the sermon, while syntactic variations through al-taqdīm wa al-ta'khīr and the repetition of the lafaz al-ghurūr emphasize the rhetorical power and emphasis of meaning. Semantic analysis reveals the use of denotative and connotative meanings as well as the use of al-ṭibāq (antonymy) techniques that enrich the expression of meaning. From a morphological perspective, the use of terms such as abnā' al-dunyā reflects the depth of contextual messages that are moral and spiritual. The element of imagery, particularly jinās, not only enhances the sound of language but also emphasizes the relationship of meaning within the discourse of sermons. The novelty of this research lies in the application of a comprehensive stylistic analysis to the sermons of the early Islamic caliphs, which have so far been studied primarily historically and thematically. This finding confirms that the linguistic beauty of Uthman ibn Affan's sermons is not merely rhetorical ornamentation, but rather an effective medium for conveying moral and spiritual messages persuasively تتناول هذه الدراسة جمال الأسلوب في خطبة عثمان بن عفان الأولى بعد توليه الخلافة الثالثة، مُسلطةً الضوء على خمسة جوانب رئيسية، هي: علم الأصوات، وعلم الصرف، وعلم النحو، وعلم الدلالة، والتصوير. وتعتمد الدراسة منهجًا نوعيًا مع تحليل أسلوبي لنص الخطبة العربية، الذي دُرِسَ وصفيًا تحليليًا. تُظهر النتائج أن غلبة الحروف الأنفية والساكنة المهتزة تُشكل إيقاعًا صوتيًا مميزًا يُعزز قوة الخطبة الإقناعية، بينما تُؤكد التنويعات النحوية من خلال